Ionospheric and geomagnetic Pc5 oscillations as observed by the ionosonde and magnetometer at Sodankylä. Issue 7 (1st April 2019) - Kozyreva, O.; Kozlovsky, A.; Pilipenko, V.; Yagova, N.
Abstract: The study is based on the data of the rapid-run ionosonde at the Sodankylä Geophysical Observatory at auroral latitude (L = 5.25) which routinely performs one-minute sounding since 2007. This dataset allows a unique opportunity for investigating possible effects of ultra-low frequency (ULF, 1–7 mHz) waves in the auroral ionosphere. Suitable observations were made during moderately disturbed geomagnetic conditions typically at recovery of the geomagnetic storms caused by solar wind high-speed streams, in the daytime between 9 and 16 MLT. The ionospheric oscillations corresponding to Pc5 geomagnetic pulsations were found in variations of the virtual height of the F layer and the power of ionosonde reflections from E and F layers. The later are most probably caused by modulation of electron precipitation, which is also manifested in weak (about 0.01–0.06 dB) variations of cosmic noise absorption. The most important and novel result is that the pulsations of power of reflection from E and F layers typically has a spectral maximum at nearly half the periodicity of the Pc5 geomagnetic pulsations, whereas such spectral peak is negligible in the geomagnetic pulsations.